Paediatric Common Infections Pathways: improving antimicrobial stewardship and promoting ambulation for children presenting with common infections to hospitals in the UK and Ireland. Issue 1 (12th March 2021) - Horner, Carolyne; Cunney, Robert; Demirjian, Alicia; Doherty, Conor; Green, Helen; Mathai, Mathew; McMaster, Paddy; Munro, Alasdair; Paulus, Stéphane; Roland, Damian; Patel, Sanjay
Abstract: Paediatric common infection pathways have been developed in collaboration between the BSAC and national paediatric groups, addressing the management of cellulitis, lymphadenitis/lymph node abscess, pneumonia/pleural empyema, pyelonephritis, tonsillitis/peritonsillar abscess, otitis media/mastoiditis, pre-septal/post-septal (orbital) cellulitis, and meningitis. Guidance for the management of a child presenting with a petechial/purpuric rash and the infant under 3 months of age with fever is also provided. The aim of these pathways is to support the delivery of high-quality infection management in children presenting to a hospital. The pathways focus on diagnostic approaches, including the recognition of red flags suggesting complex or severe infection requiring urgent intervention, approaches to antimicrobial stewardship (AMS) principles and guidance on safe and timely ambulation aligned with good practice of outpatient parenteral antimicrobial therapy (OPAT).